Pengaruh regional brand ambassador dan social media advertising terhadap brand trust dan brand loyalty konsumen gen-Z - Silva Aniyah Zafira; Arnolt Kristian Pakpahan (Jurnal Syntax Admiration, 2025)
In today's digital era, competition in the E-Commerce Shopee Live, Tokopedia Live, Tiktok Live, dan Lazada Live industry is becoming increasingly fierce, prompting companies to develop effective marketing strategies to enhance consumer trust and loyalty. As a leading player in this industry, E-Commerce Shopee Live, Tokopedia Live, Tiktok Live, dan Lazada Live seeks to understand how the use of Regional Brand Ambassadors and Social Media Advertising can influence Brand Trust and Brand Loyalty among Generation Z consumers. This study aims to analyze the impact of Regional Brand Ambassadors and Social Media Advertising on Brand Trust and Brand Loyalty among E-Commerce Shopee Live, Tokopedia Live, Tiktok Live, dan Lazada Live’s Generation Z consumers. A total of 185 Generation Z respondents from Jakarta participated in this survey. The collected data was analyzed using SmartPLS v.3 to ensure the validity, reliability, and accuracy of the tests in this study. The results showed that both Regional Brand Ambassadors and Social Media Advertising have a positive impact on Brand Trust and Brand Loyalty, and that Brand Trust positively affects Brand Loyalty. Moreover, Brand Trust is able to mediate the impact between Regional Brand Ambassadors and Social Media Advertising on Brand Loyalty.